Effect of Ganoderma lucidum polysaccharides as immunostimulants against Vibrio harveyi in pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus lanceolatus) - Zhang, Yilin; Zhong, Jian; Huang, Yucong; Jian, Jichang; Cai, Shuanghu (Frontiers in Marine Science, 2022)
Immunostimulants are becoming one of the most effective models for healthy and sustainable development against vibriosis, which is a serious threat to the global aquaculture industry. This study evaluated the effects of different concentrations of Ganoderma lucidum polysaccharides (GLPs) on immunomodulatory and disease resistance of pearl gentian groupers. The relative percent survival of the pearl gentian groupers challenged with Vibrio harveyi ZJ0603 by intraperitoneal injection reached 53.3%, 60%, 70% and 73.3% in GLPs2, GLPs4, GLPs6 and GLPs8 group, respectively, significantly higher than that of 33.3% in control group. Meanwhile, the expression levels of immune-relative genes, including IgM, MHC-Iα, MHC2, IL-1β and TNF-α, were up-regulated in liver, spleen, head kidney and thymus within 28 d post GLPs injection. Total serum protein and the activities of catalase, superoxide dismutase, and lysozymes in serum were significantly up-regulated in all GLPs groups compared with those in the control. Moreover, the optimal immunity effect was observed with injection of GLPs at concentrations of 6 or 8 mg/ml. The results demonstrate that GLPs was an effective immunostimulant enhancing both specific and non-specific immunity as well as disease resistance in pearl gentian grouper.